Strengthening the meaning in life among college students: the role of self-acceptance and social support - evidence from a network analysis - Wu, Caiyun; Liu, Xueting; Liu, Jinxin; Tao, Yanqiang; Li, Yuting (Frontiers in Psychology, 2024)
Meaning in life, which has two possible sources: self-acceptance and social support, is essential to the mental health and development of college students. The current study aims to further clarify the symptom-level relations between meaning in life, self-acceptance, and social support, finding possible ways to improve meaning in the life of college students. 1,348 Chinese college students completed the online questionnaire, including Self-acceptance Questionnaire, Social Support Rating Scale, and Meaning in Life Questionnaire and the data from 1263 participants was used. Cross-sectional network analysis was used to examine the relation between self-acceptance and social support. We also explored the relation between dimensions of self-acceptance and social support and meaning in life using the flow network. The results show symptom “SlA” (self-acceptance) is the bridge symptom linking self-acceptance and social support. In the flow diagrams, “SlA” is directly and positively associated with the presence of meaning. Objective Support shares the strongest positive association with the search for meaning. The symptom “SIA” may be an important targeting symptom when trying to improve the meaning in life of college students. Additionally, social support is essential for college students to develop meaning in life.